Pengaruh Kemudahan dan Kepercayaan Terhadap Kepuasan dan Loyalitas pada Transportasi Maxim - Fauz Rafid Syafiq; Bambang Sutejo; Sri Sumiyati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to test the effect of convenience and trust on satisfaction and loyalty with Maxim transportation, with 100 respondents. The data analysis method uses multiple linear regression with the SPSS program. The results of the research easily have a positive and significant effect on Maxim Transportation customer satisfaction, trust has a positive and significant effect on Maxim Transportation customer satisfaction. Research findings reveal that the majority of respondents have used online transportation, customer satisfaction has a positive and significant effect on maximal transportation loyalty.